2010
DOI: 10.1097/mbc.0b013e328337b39f
|View full text |Cite
|
Sign up to set email alerts
|

Ephedra alkaloids inhibit platelet aggregation

Abstract: Sympathomimetics, such as Ephedra alkaloids, are associated with an increased incidence of intracerebral hemorrhage believed to be secondary to concomitant elevations in blood pressure. We hypothesized that sympathomimetics decrease platelet aggregation. Reductions in epinephrine-mediated platelet aggregation by ephedrine, phenylpropanolamine, and racemic amphetamine were determined by measuring the changes that these sympathomimetics induced in the optical density of platelet-rich plasma from healthy individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
5
0
2
Order By: Relevance
“…We sought to identify pharmacologic antagonists that could modify the behavior outcomes of social stress that often results in emotional eating and unhealthy weight gain. We have shown that many of the effects of the stress hormone, epinephrine, through α2AR signal transduction are mediated by carbonic anhydrase-dependent chloride/bicarbonate exchange [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We sought to identify pharmacologic antagonists that could modify the behavior outcomes of social stress that often results in emotional eating and unhealthy weight gain. We have shown that many of the effects of the stress hormone, epinephrine, through α2AR signal transduction are mediated by carbonic anhydrase-dependent chloride/bicarbonate exchange [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…These effects of the amphetamine could be due to the inhibition by these sympathomimetics of central α2ARs in the paraventricular hypothalamus (PVH) that modify satiety and locomotion [ [13] , [14] , [15] , [16] , [17] , [18] ]. As noted above, we have previously shown that α2AR signal transduction can be inhibited by blocking carbonic anhydrase-dependent chloride/bicarbonate transport with acetazolamide in platelets and vascular smooth muscle [ 22 , 23 ]. In this current report, we show that acetazolamide demonstrates potent anorectic properties, increases locomotion, and diminishes weight gain during exposure to social stress similar to the action of amphetamines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A biztonságos felhasználásnak előfeltétele a készítmény összetevőinek alapos ismerete, melynek figyelmen kívül hagyásával alkalmazásuk számos gyógyszer-interakciót és szövődményt okozhat [20,21]. A gyógynövények esetén fokozottan számolni kell e veszélyeikkel a perioperatív ellátás kapcsán, mellékhatásaik érinthetik a véralvadás rendszerét, a szív-és érrendszert, a hormonális rendszert, a vese-és májműködést [22][23][24][25][26][27][28][29].…”
Section: Gyógynövények Alkalmazása Járvány Idejénunclassified
“…Ismerni kell mind a hatóanyagokat, mind azok élettani és terápiás hatásait, melyek figyelmen kívül hagyásával alkalmazásuk számos gyógyszer-interakciót és szövődményt hozhat létre [1][2][3]. Többféle gyógynövény esetében merült fel potenciálisan káros hatásuk a haemostasisra [4][5][6], a cardiovascularis rendszerre [7,8], az endokrin rendszerre, a máj-és veseműködésre [9,10].…”
unclassified